RANCANG BANGUN SISTEM INFORMASI PENGOLAHAN NILAI AKHIR PER MATA PELAJARAN PADA SMK PGRI 11 JAKARTA - Setiabudi, Arifin; Setiady, Teddy; Rustanto, Agung Edi; Winarti, Euis (POLITEKNIK LP3I JAKARTA, 2020)
The value processing process used at SMK PGRI 11 in Jakarta is currently still using the manual method, namely by filling in the values in Microsoft Office Excel given by the school principal, so that in data collection and processing the employee's ability values are not effective and efficient. From these problems led to the idea to create a Desktop-based information system, in which it can perform computerized data management and value processing. The research method used is Library Research and Field Research. The application software used is SQL Server, VB.NET, Microsoft Office Word 2010, StarUML, draw.io. There are two actors/users in this information system, namely Admin and homeroom teacher. It is hoped that the existence of a value processing information system in the form of a Desktop can facilitate the process of data management and value processing in this school. Keywords: Information System, Value Processing, Final Value